Uniform Opial properties in generalized Cesàro sequence spaces - Petrot N. (2014)
The main purpose of this paper is considering the generalized Cessàro sequence spaces defined by S. Suantai [On some convexity properties of generalized Cessàro sequence spaces, Georgian Math. J. 10(1) (2003) 193-200] by giving some topological properties and finding condition for ces(p) equipped with both the Amemiya norm and the Luxemburg norm to possesses uniform Opial property. © 2005 Elsevier Ltd. All rights reserved.